Analisis Perlindungan Hukum terhadap Bank dalam Kasus Wanprestasi Pembayaran Utang oleh Nasabah: Studi Kasus Putusan Nomor 7/Pdt.G.S/2023/Pn Bta - Nethania Aurelia Madelin; Angelina Jacqueline Sugiarto; Jessica Chua (CV Rewang Rencang, 2025)
A credit agreement is a form of civil obligation that binds the creditor and debtor in a mutually beneficial legal relationship. However, in practice, defaults by customers often occur, leading to financial losses and affecting the stability of banks as lenders. This study aims to analyze the legal certainty provided by regulations in resolving default disputes between banks and customers, as well as to assess the fairness of legal protection for both parties. By using normative legal research methods and a case study of Batam District Court Decision Number 7/Pdt.G.S/2023/PN Bta, it was found that the existing regulations have not fully provided balanced legal protection. Banks often do not receive proportional compensation despite winning the case. Additionally, there is an imbalance in the execution of collateral and limited access for customers to non-litigation dispute resolution mechanisms. Therefore, banking policy reforms are needed, including strengthening regulations, applying the principle of caution in collateral execution, and providing legal education for customers. With a more balanced approach, it is hoped that a fair legal system can be created for both banks and customers in default cases.